KAJIAN PERUBAHAN DAN VOLATILITAS HARGA KOMODITAS PANGAN STRATEGIS SERTA PENGARUHNYA TERHADAP INFLASI DI KOTA BANDA ACEH - Pradana, Reza Septian (EP FEB UNS, 2019)
This study aims to analyze the price change and volatility of strategic food commodities and the influence to inflation in Banda Aceh City. Food commodities in this study are restricted to rice, onion, red chili, and small chili. To identify the existance of strategic food commodities’ price volatility, this study uses ARCH/GARCH model. Then, this study uses further analysis by using multiple regression to know the influence of strategic food commodities’ price change and volatility to inflation in Banda Aceh City. The result of ARCH-LM test shows that price volatility is existed in the price change of rice and onion. Then, result of multiple resgression estimation shows that the price change of rice, onion, red chili, and small chili significantly have positive influence to inflation in Banda Aceh City. Price volatility of rice and onion insignificantly influent to inflation in Banda Aceh City. Thus, government should protect the price stabilty of strategic food commodities, especially rice, onion, red chili, and small chili in order to keep in mild inflation. Keyword: ARCH/GARCH, inflation, strategic food commodities, multiple regression, price volatility